Molecular epidemiology and genetic diversity of Listeria monocytogenes isolates from a wide variety of ready-to-eat foods and their relationship to clinical strains from listeriosis outbreaks in Chile - Montero, David; Bodero, Marcia; Riveros, Guillermina; Lapierre, Lisette; Gaggero, Aldo; Vidal, Roberto M.; Vidal, Maricel (Frontiers in Microbiology, 2015)
Listeria monocytogenes is a pathogen transmitted through food that can cause severe infections in high-risk groups such as pregnant women, elderly, young children and immunocompromised individuals. It is a ubiquitous bacterium that can survive in harsh conditions, such as dry environments, at low temperatures, in brine conditions and at low pH values. It also has the capacity to form biofilms, which makes it particularly successful even in colonizing surfaces within food processing plants. This study analyzed the presence of L. monocytogenes in ready-to-eat food (RTE) such as sausage, cheese, fresh salads and other types of raw food. 850 samples of refrigerated and packaged food collected in 2008 and 2009 were analyzed. It was found that 25% of these samples were contaminated with L. monocytogenes strains. Serotyping and virulence genes detection by polymerase chain reaction (PCR) identified that strains belonging to serotype 4b, and containing one or more genes encoded by LIPI-1, were significantly associated with specific food types. Furthermore, using pulse field gel electrophoresis (PFGE), it was possible to associate isolates from cheese with strains from clinical cases of listeriosis outbreaks that occurred during the same time period within the same geographic regions. In addition, a strong correlation was observed between isolates from frozen seafood and from clinical strains obtained from sporadic cases of listeriosis. In agreement with reports described in other countries, our results shown that Chilean strains of L. monocytogenes from food products include the most virulent serotypes, encoding for the main virulence genes of the LIPI-1 pathogenicity island, and were clonally related to clinical isolates from sporadic cases and outbreaks of listeriosis. In conclusion, we show that Chilean isolates of L. monocytogenes from RTE and raw food products can cause disease in humans, representing a public health risk that justifies permanent surveillance.